(untitled) (Huellas, 2024)
The agribusiness model involved the expansion of crops and the application of a technological package that has generated the use of millions of liters of agrochemicals, which exposes rural populations to simultaneous or sequenced exposure to products, which seriously affect health and the environment. These externalities are reflected in the body-territory of women who inhabit and/or transit rural spaces, and suffer from daily land dispossession, labor exploitation and deterioration of their health as a result of the drift of agrochemicals. In this paper I intend to make visible the struggle of women, teachers, who gave birth to the Federal Network of Teachers for Life in San Andrés de Giles (Buenos Aires province) in 2017; an environmental group that denounces these problems, promotes actions to protect the environment and the rights of students and rural families. The methodology includes the analysis of journalistic sources, fieldwork and the development of semi-structured interviews in the territory of San Andrés de Giles.